2005
DOI: 10.1111/j.1365-2958.2005.04662.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial ribosomal RNA in pieces

Abstract: SummaryThe exact knowledge on the ribosomal RNA (rRNA) structure is an important prerequisite for work with rRNA sequences in bioinformatic analyses and in experimental research. Most available rRNA sequences of bacteria are based on gene sequences and on similarity analyses using Escherichia coli rRNA as a standard. Therefore, it is often overlooked that many bacteria harbour mature rRNA 'in pieces'. In some cases, the processing steps during the fragmentation lead to the removal of rRNA segments that are usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 56 publications
(115 reference statements)
7
52
0
Order By: Relevance
“…1). Unlike with introns, the IVS is excised from the RNA without exon ligation, a cleavage process mediated by RNase III (8), resulting in a fragmented but functional rRNA. Moreover, unlike with other obligate intracellular bacteria, which have few or no insertion sequencespresumably due to limited opportunities for lateral gene transfer-C. burnetii's genome possesses a large number of insertion sequence elements (29 full-length and 3 degenerate).…”
Section: Discussionmentioning
confidence: 99%
“…1). Unlike with introns, the IVS is excised from the RNA without exon ligation, a cleavage process mediated by RNase III (8), resulting in a fragmented but functional rRNA. Moreover, unlike with other obligate intracellular bacteria, which have few or no insertion sequencespresumably due to limited opportunities for lateral gene transfer-C. burnetii's genome possesses a large number of insertion sequence elements (29 full-length and 3 degenerate).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is reported that tRNA cleavage is a response to stresses in the Eukaryota (15,56), and cancer-or ageassociated changes in fragmented tRNAs have been observed (27,32). Recently, rRNA fragmentation has become another topic of interest (16,39), although the functions of fragmented rRNAs remain unclear. Papers that report unique RNA regulatory sequences, called riboswitches, in prokaryotic cells also are accumulating (49).…”
mentioning
confidence: 99%
“…The rrn operon is one of the most widely studied operons in the bacterial genome having been studied at the level of ribosome structure (Gutell, Lee, & Cannone, 2002;Wimberly et al, 2000), ribosomal RNA (rRNA) gene transcription (Condon, Squires, & Squires, 1995;Evguenieva-Hackenberg, 2005), rRNA gene organisation (Martín, Barreiro, González-Lavado, & Barriuso, 2003), rrn operon organisation at the level of the bacterial whole genome (Gurtler & Grando, 2013) and the use of the 16S rRNA gene sequence in evolutionary and phylogenetic studies, pioneered by Woese (1987). Indeed, the 16S rRNA gene sequence database is the cornerstone of evolutionary phylogenetics and bacterial taxonomy (Amann, Ludwig, & Schleifer, 1995;Baker, Smith, & Cowan, 2003;Woese, 1987).…”
Section: Introductionmentioning
confidence: 99%